2014
DOI: 10.1111/btp.12167
|View full text |Cite
|
Sign up to set email alerts
|

The Seed and Fern Spore Bank of a Recovering African Tropical Forest

Abstract: Seed banks contribute to forest regeneration after disturbance, but less is known about fern spore banks, particularly in a paleotropical context. We sampled the buried seed and fern spore bank in Mabira Forest, a 300 km 2 forest in central Uganda, to explore the effect of time since disturbance. Soil cores (5 cm depth) were taken from 39 plots across three different classes of 'recovery': (1) not disturbed since 1950; (2) logged between 1950 and 1980; and (3) cleared for agriculture between 1970 and 1990 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…These patterns may be due to the fern's reproduction mode. Viable 'spore banks' have been identified for at least some fern species (Penrod & Mccormick 1996;Ram ırez-Trejo et al 2004;Esaete et al 2014), and it is possible that Gleichenia gametophytes were overlooked, especially as they look superficially similar to liverworts which were present. However, seed/spore bank recovery is much more common in angiosperms, and it is more likely that Gleichenia relies solely on resprouting for early regeneration as other studies have suggested (Walker & Boneta 1995;Clarkson 1997;Mcqueen & Forester 2000).…”
Section: Implications For Plant Community Dynamics Of New Zealand Res...mentioning
confidence: 99%
“…These patterns may be due to the fern's reproduction mode. Viable 'spore banks' have been identified for at least some fern species (Penrod & Mccormick 1996;Ram ırez-Trejo et al 2004;Esaete et al 2014), and it is possible that Gleichenia gametophytes were overlooked, especially as they look superficially similar to liverworts which were present. However, seed/spore bank recovery is much more common in angiosperms, and it is more likely that Gleichenia relies solely on resprouting for early regeneration as other studies have suggested (Walker & Boneta 1995;Clarkson 1997;Mcqueen & Forester 2000).…”
Section: Implications For Plant Community Dynamics Of New Zealand Res...mentioning
confidence: 99%